2012
DOI: 10.1152/ajpregu.00006.2012
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory muscle fatigue increases sympathetic vasomotor outflow and blood pressure during submaximal exercise

Abstract: Katayama K, Iwamoto E, Ishida K, Koike T, Saito M. Inspiratory muscle fatigue increases sympathetic vasomotor outflow and blood pressure during submaximal exercise. Am J Physiol Regul Integr Comp Physiol 302: R1167-R1175, 2012. First published March 28, 2012 doi:10.1152/ajpregu.00006.2012.-The purpose of this study was to elucidate the influence of inspiratory muscle fatigue on muscle sympathetic nerve activity (MSNA) and blood pressure (BP) response during submaximal exercise. We hypothesized that inspirato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
115
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(126 citation statements)
references
References 46 publications
9
115
1
1
Order By: Relevance
“…This study showed that NDI was more effective in the experimental group. Katayama et al21 ) reported that proper breathing can release the body by stimulating activity of the sympathetic nervous system, and Kim et al22 ) reported that neck pain and NDI improved after mediating active release techniques for 3 weeks for 24 patients with chronic neck pain. based on these studies, when breathing exercises are mediated, they are effective in releasing the body.…”
Section: Discussionmentioning
confidence: 99%
“…This study showed that NDI was more effective in the experimental group. Katayama et al21 ) reported that proper breathing can release the body by stimulating activity of the sympathetic nervous system, and Kim et al22 ) reported that neck pain and NDI improved after mediating active release techniques for 3 weeks for 24 patients with chronic neck pain. based on these studies, when breathing exercises are mediated, they are effective in releasing the body.…”
Section: Discussionmentioning
confidence: 99%
“…Maximal inspiratory pressure, which is commonly used to measure inspiratory muscle strength, was assessed according to the published guidelines (2). Maximal inspiratory pressure was measured before whole-body warm-up and within 2 minutes after completion of the 400-and 800-m running tests, using a portable autospirometer (AS-507; Minato Medical Science, Osaka, Japan) with a handheld mouth pressure meter (AAM377; Minato Medical Science) (18). All measurements were made while the participants sat with their nose occluded.…”
Section: Methodsmentioning
confidence: 99%
“…Pulmonary function was assessed using a portable autospirometer (AS-507; Minato Medical Science) (18) to determine forced vital capacity (FVC) and forced expiratory volume in 1 second (FEV 1 ). All measurements were performed according to the published guidelines (22).…”
Section: Methodsmentioning
confidence: 99%
“…MIP was measured before the whole-body warm-up, and within 2 min after completion of the MART and maximal intermittent graded exercise tests, using a portable autospirometer (AS-507; Minato Medical Science) with a handheld mouth-pressure meter (AAM377; Minato Medical Science) [14]. All measurements were made while the participant sat with her nose occluded.…”
Section: Mip Proceduresmentioning
confidence: 99%
“…Pulmonary function was assessed using a portable autospirometer (AS-507; Minato Medical Science) [14] to determine forced vital capacity (FVC) and forced expiratory volume in 1 s (FEV 1 ). All measurements were performed according to published guidelines [16].…”
Section: Pulmonary-function Testingmentioning
confidence: 99%